Geochemistry and Zircon U-Pb Dates of Felsic-Intermediate Members of the Late Cretaceous Yuksekova Arc Basin: Constraints on the Evolution of the Bitlis-Zagros Branch of Neotethys (Elazig, E Turkey) - Ural, Melek; Sayit, Kaan; Koralay, Osman Ersin; Goncuoglu, Mehmet Cemal (Wiley, 2021)
During the Late Cretaceous in the Eastern Mediterranean, the northern branch of the southern Neotethys was closed by multiple northward subductions. Of these, the most northerly located subduction created the Baskil continental arc at around 82-84 Ma. The more southerly and intra-oceanic subduction, on the other hand, produced an arc-basin system, the Yuksekova Complex, as early as the late Cenomanian-early Turonian. The abundant and relatively well-studied basaltic rocks of this complex were intruded by dykes, sills and small stocks of felsic-intermediate rocks, not previously studied in detail. The intrusives collected from five different localities in the Elazig region of eastern Turkey are all subalkaline, with low Nb/Y values. Most of them have been chemically classified as rhyodacites/dacites, whereas a small number appear to be andesites. In normal mid-ocean-ridge basalt (N-MORB)-normalised plots, the intrusives are characterised by relative enrichments in Th and La over Nb, Zr, Hf, Ti and high field strength elements (HREEs), indicating their derivation from a subduction-modified source. While their relatively high, positive epsilon(Nd)(i) values (+6.4 and +7.2) might suggest a depleted mantle source for their ultimate origin, somewhat radiogenic Pb values indicate a sedimentary contribution to the source of the rocks. The overall geochemical characteristics indicate their generation in an oceanic arc setting. The zircon U-Pb Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) data obtained from five felsic-intermediate rock samples yielded intrusion dates of 80-88 Ma. This suggests that the Elazig oceanic arc-related intrusives are slightly younger than those of the Yuksekova arc-basin system, but coeval with the Baskil continental arc. However, the felsic-intermediate intrusives show different geochemical characteristics (oceanic arc-type, with a lack of crustal contamination) to those of the Baskil continental arc. This indicates that these two igneous systems are unrelated and likely developed in different tectonic settings. This, in turn, supports a geodynamic model in which the northern strand of the southern Neotethys was consumed by multiple northward subductions.
Keywords: petrography; geochronology; felsic magmatism; multiple subduction; Yuksekova arc basin; Neotethys; Turkey